Volatile compounds, physicochemical and sensory characteristics of Colatura di Alici, a traditional Italian fish sauce. (27th April 2020) - Russo, Giovanni L; Langellotti, Antonio L; Genovese, Alessandro; Martello, Anna; Sacchi, Raffaele
Abstract: BACKGROUND: The present study reports for the first time the physical, chemical and sensory characterization of a traditional fish sauce from Italy, called ' Colatura di Alici ', which is considered to be the direct descendant of the ancient roman sauce ' Garum '. RESULTS: Among the volatile compounds, carboxylic acids, aldehydes, sulphuric compounds and pyrazines were identified. The most abundant compounds identified were 3‐methyl‐butanoic acid, nonanal and 3‐methyl‐butanal. The sample A had the highest amount of volatile fatty acids (>250 μg kg −1 ) and sample B had the highest concentration of aldehydes (>80 μg kg −1 ). These volatile compounds arise from the long fermentation activity and oxidation of fatty acids of the fish flesh and are responsible for the strong cheesy and fishy aroma. The protein content ranged from 90 to 130 g kg −1, and the soluble solids ranged from 30 to 38 °Brix, as a result of the high amount of NaCl used during processing. The sensory analysis showed a great intensity for the cheesy, fishy and umami attributes, and a medium intensity for the roasted and meaty attributes. CONCLUSION: For the first time, the volatile compounds and sensory characteristics of this traditional fish sauce are reported. The samples differ in terms of sensory and aromatic profiles. These differences are probably linked to the poorly standardized methods used in the production process. Overall, the results of the present study could be used by local fish sauce producers to monitor the quality of the product and to improve the production process. © 2020 Society of Chemical Industry